Association of 1078 del T cystic fibrosis mutation with severe disease. Issue 2 (February 1994) - Moullier, P; Jéhanne, M; Audrézet, M P; Mercier, B; Verlingue, C; Quéré, I; Guillermit, H; Raguénès, O; Storni, V; Rault, G
Abstract : Apart from the high frequency of the delta F508 mutation (81.81%) in Breton cystic fibrosis chromosomes, one mutation, 1078 del T, is also observed frequently (4.96%) in this group, in comparison with the rest of the French where it occurs with a frequency of 0.57%. These two mutations account for more than 86.5% of the total CF mutations identified on Breton chromosomes. We have conducted an unblinded retrospective analysis of 25 patients with the 1078 del T mutation and compared their phenotypes with those of a group of 70 delta F508 homozygous patients. Both groups of patients had the same ethnic origin and were regularly attending the same CF centre in Brittany, which makes this sample highly homogeneous despite the small size. The 1078 del T mutation appeared to be associated with severe presentation of the disease with, however, a trend to reduced mortality and less Pseudomonas aeruginosa colonisation.